Putative lateral inhibition in sensory processing for directional turns - Yafremava, Liudmila S. (American Physiological Society, 2011)
Computing targeted responses is a general problem in goal-directed behaviors. We sought the sensory template for directional turning in the predatory sea slug Pleurobranchaea californica, which calculates precise turn angles by averaging multiple stimulus sites on its chemotactile oral veil (Yafremava LS, Anthony CW, Lane L, Campbell JK, Gillette R. J Exp Biol 210: 561–569, 2007). Spiking responses to appetitive chemotactile stimulation were recorded in the two bilateral pairs of oral veil nerves, the large oral veil nerve (LOVN) and the tentacle nerve (TN). The integrative abilities of the peripheral nervous system were significant. Nerve spiking responses to punctate, one-site stimulation of the oral veil followed sigmoid relations as stimuli moved between lateral tentacle and the midline. Receptive fields of LOVN and TN were unilateral, overlapping, and oppositely weighted for responsiveness across the length of oral veil. Simultaneous two-site stimulation caused responses of amplitudes markedly smaller than the sum of corresponding one-site responses. Plots of two-site nerve responses against the summed approximate distances from midline of each site were markedly linear. Thus the sensory paths in the peripheral nervous system show reciprocal occlusion similar to lateral inhibition. This outcome suggests a novel neural function for lateral inhibitory mechanisms, distinct from simple contrast enhancement, in computation of both sensory maps and targeted motor actions.